Pengaruh Karantina Di Era Pandemi Covid-19 Terhadap Aspek Psiko-Sosial Masyarakat - Angelika, Michelle; Utomo, Laksanto (Program Studi Ilmu Hukum Fakultas Hukum dan Ilmu Sosial Universitas Pendidikan Ganesha Singaraja, 2021)
The COVID-19 pandemic in Indonesia has had a huge impact on Indonesian society from health, legal, social, and other perspectives. With the rapid spread of the virus, the government is close to preventing and controlling the COVID-19 pandemic as early as possible. One of the measures taken is the Indonesian Government Regulation Number 21 of 2020. This is in line with the concept of Utilitarianism, which emphasizes benefits. But on the other hand, people are also social creatures who are accustomed to socializing with other communities. When facing the COVID-19 pandemic, people are ordered to isolate themselves for a prolonged period, impacting psychosocial changes. The Indonesian government determines the status of a community emergency through Presidential Decree No. 11 of 2020